A comparison of miRNA isolation and RT-qPCR technologies and their effects on quantification accuracy and repeatability. (March 2013) - Redshaw, Nicholas; Wilkes, Timothy; Whale, Alexandra; Cowen, Simon; Huggett, Jim; Foy, Carole A.
MicroRNAs (miRNAs) are short (∼22 nucleotides), non-coding RNA molecules that post-transcriptionally regulate gene expression. As the miRNA field is still in its relative infancy, there is currently a lack of consensus regarding optimal methodologies for miRNA quantification, data analysis and data standardization. To investigate miRNA measurement we selected a panel of both synthetic miRNA spikes and endogenous miRNAs to evaluate assay performance, copy number estimation, and relative quantification. We compared two different miRNA quantification methodologies and also assessed the impact of short RNA enrichment on the miRNA measurement. We found that both short RNA enrichment and quantification strategy used had a significant impact on miRNA measurement. Our findings illustrate that miRNA quantification can be influenced by the choice of methodology and this must be considered when interpreting miRNA analyses. Furthermore, we show that synthetic miRNA spikes can be used as effective experimental controls for the short RNA enrichment procedure.